Ectonucleotidases in Intestinal and Hepatic Inflammation - Vuerich, Marta; Robson, Simon C.; Longhi, Maria Serena (Frontiers in Immunology, 2019)
Purinergic signaling modulates systemic and local inflammatory responses. Extracellular nucleotides, including eATP, promote inflammation, at least in part via the inflammasome upon engagement of P2 purinergic receptors. In contrast, adenosine generated during eATP phosphohydrolysis by ectonucleotidases, triggers immunosuppressive/anti-inflammatory pathways. Mounting evidence supports the role of ectonucleotidases, especially ENTPD1/CD39 and CD73, in the control of several inflammatory conditions, ranging from infectious disease, organ fibrosis to oncogenesis. Our experimental data generated over the years have indicated both CD39 and CD73 serve as pivotal regulators of intestinal and hepatic inflammation. In this context, immune cell responses are regulated by the balance between eATP and adenosine, potentially impacting disease outcomes as in gastrointestinal infection, inflammatory bowel disease, ischemia reperfusion injury of the bowel and liver, autoimmune or viral hepatitis and other inflammatory conditions, such as cancer. In this review, we report the most recent discoveries on the role of ENTPD1/CD39, CD73 and other ectonucleotidases in the regulation of intestinal and hepatic inflammation. We discuss the present knowledge, highlight the most intriguing and promising experimental data and comment on important aspects that still need to be addressed to develop purinergic-based therapies for these important illnesses.